ORIENTALISAM AND HUSSEINI RITUALS - Ishaq Naqqash; Afaaq Lazim abd Altief; Mushtaq Mal Allah Qasim (Galaxy International Interdisciplinary Research Journal, 2024)
Since the Arab world began to learn about Islam until the present time, Orientalist studies and their intellectual and cognitive foundations in studying relevant topics in the Islamic faith, hardly leave a topic related to the objective vision, and this is the practice of most religious aspect without approaching its study, with a non Orientalists, even if it is... There are those who do justice to Islam, but they are few